The Methodology of the Development of the Worldview of Schoolchildren through Games - Nurgul Shadiyeva3, Rakhat Yelubayeva4, Аlmagul Аkazhanova1, Saule Nurgali2, Meruyert Alibayeva2, (Opción, 2019)
The aim of the study is to investigate the methodology of thedevelopment of the worldview of schoolchildren through games viacomparative qualitative research methods. As a result, proper andhighquality use of national games in the field of education depends onthe exact definition of their place and duty at each period of lessonsand goals. In conclusion, the duty of every teacher is to enlighten thecenturies-old national heritage of our country through training andeducation, to promote forgotten traditions and national identity, and toform among them the national psychology.